Doctor Who: Season Three Complete season three - Collinson, Phil; Agyeman, Freema, 1979-; Barrowman, John, 1967-; Davies, Russell T.; Harper, Graeme, 1945-; Lyn, Euros; Tennant, David, 1971-; Page, Adam; Evans, Geoff; BBC Video (Firm); Canadian Broadcasting Corporation; Warner Home Video (Firm) ([London] : BBC Worldwide ; Burbank, CA : distributed by Warner Home Video, 2012)
Martha Jones, a young medical doctor finds herself and her entire hospital transported to the moon! Confronted with some nasty aliens Martha's only hope for survival appears to be a man who calls himself The Doctor. So begins the third and most exciting season yet of the new Doctor Who. As the Doctor's new companion Martha Jones will encounter everything from William Shakespeare to the Doctor's arch-nemesis. It will definitely be the experience of a lifetime.
Disc 1. Runaway bride -- Disc 2. Smith and Jones -- Shakespeare code -- Gridlock -- Disc 3. Daleks in Manhattan -- Evolution of the Daleks -- Lazarus experiment -- 42 -- Disc 4. Human nature -- Family of blood -- Blink -- Disc 5. Utopia -- Sound of drums -- Last of the time lords -- Disc 6. Doctor Who confidential.
Originally produced for television broadcast in 2006 and 2007.
Distributed under license from 2 Entertain Ltd & BBC Worldwide/BBC Video.
Special features: Music and monsters; Freema's tour of the studio; David Tennant's video diaries; Deleted scenes; Outtakes; audio commentary; teaser trailers.
Original theme music, Ron Grainer ; music, Murray Gold ; directors of photography, Rory Taylor, Ernie Vincze, ; editors, John Richards, Matthew Tabern, Mike Jones, Will Oswald, Jamie McCoan, Mike Hopkins.
David Tennant, Freeman Agyeman, Catherine Tate, John Barrowman.
Not rated, CHV PG.
Keywords: Doctor -- (Fictitious character) -- Drama; Doctor -- (Fictitious character).; Human-alien encounters -- England -- London -- Drama; Time travel -- Drama; Television programs -- Great Britain; Human-alien encounters; Time travel; London (England) -- Drama; Action and adventure television programs; Video recordings; Drama; Science fiction television programs